2016
DOI: 10.1051/matecconf/20179201003
|View full text |Cite
|
Sign up to set email alerts
|

Research of power fuel low-temperature vortex combustion in industrial boiler based on numerical modelling

Abstract: The goal of the presented research is to perform numerical modelling of fuel low-temperature vortex combustion in once-through industrial steam boiler. Full size and scaled-down furnace model created with FIRE 3D software and was used for the research. All geometrical features were observed. The baseline information for the low-temperature vortex furnace process are velocity and temperature of low, upper and burner blast, air-fuel ratio, fuel consumption, coal dust size range. The obtained results are: tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Flows directed towards each other and form a couple of forces. It creates a vortex motion in the lower part of the furnace [2]. …”
Section: Air and Recirculation Modesmentioning
confidence: 99%
“…Flows directed towards each other and form a couple of forces. It creates a vortex motion in the lower part of the furnace [2]. …”
Section: Air and Recirculation Modesmentioning
confidence: 99%
“…Ash and slag accumulates on the heating surfaces and thereby prevents heat output. Therefore, boiler requires higher fuel consumption to maintain the operating conditions [2,3]. We consider a furnace pipe to have a layer of deposits on its surface.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…This method of burning is interesting that in his study has identified a number of advantages: stabilization of ignition and combustion, increase thermal efficiency, reduce slagging and contamination of working surfaces, the reduction of emissions of nitrogen oxides and sulfur [1].…”
Section: Introductionmentioning
confidence: 99%